Pengaruh Komunikasi terhadap Efektivitas Penerapan Prinsip Manajemen Kantor dalam Pengelolaan Kegiatan Belajar pada Mahasiswa Jurusan Administrasi Niaga Politeknik Negeri Bandung - Nabila Zahra Nurjanah; Keysha Nadhiera Putrya (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to determine the impact of communication on the effectiveness of the implementation of office management principles (POAC) in managing learning activities for students in the Business Administration Program at Politeknik Negeri Bandung. This research uses a descriptive quantitative approach with simple linear regression analysis. Data was collected through a questionnaire consisting of 26 items measured with a Likert scale. The results show that communication has a significant impact on the effectiveness of the implementation of POAC. Overall, the regression model indicates that communication explains 49.9% of the variance in POAC effectiveness. These findings suggest that good communication plays an important role in improving the effectiveness of learning activities through better planning, organizing, actuating, and controlling